Pengaruh Profitabilitas, Struktur Aset, Likuiditas, Pertumbuhan Penjualan Dan Leverage Terhadap Struktur Modal - Fathiya Luthfita; Hesty Ervianni Zulaecha; Imam Hidayat; Sigit Budi Santoso (FEB Universitas Maritim Semarang, 2022)
This study aims to examine the effect of profitability, asset structure, liquidity and sales growth on the capital structure of food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange (1DX). The research time period used was 6 years, 2016-2021. The population of this study includes manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (BEI) for the 2016-2021 period. The sampling technique used purposive sampling. Based on the predetermined criteria, 10 companies were obtained from manufacturing companies in the food and beverage sub-sector. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis using Eviews software version 12.0. The panel data regression model used is the Random Effect Model. In this study, the dependent variable is capital structure (Y) and the independent variable is profitability (X1), asset structure (X2), liquidity (X3), sales growth (X4) and leverage (X5). The results of his research indicate that the independent variables (profitability, asset structure, liquidity, sales growth and operating leverage) have a simultaneous effect on the dependent variable on capital structure. Partially the asset structure and leverage has a positive effect, while profitability, liquidity and sales growth have no effect on the capital structure.